The Murine Angiotensin II-Induced Abdominal Aortic Aneurysm Model: Rupture Risk and Inflammatory Progression Patterns - Cao, Richard Y.; St. Amand, Timothy; Ford, Matthew D.; Piomelli, Ugo; Funk, Colin D. (Frontiers in Pharmacology, 2010)
An abdominal aortic aneurysm (AAA) is an enlargement of the greatest artery in the body defined as an increase in diameter of 1.5-fold. AAAs are common in the elderly population and thousands die each year from their complications. The most commonly used mouse model to study the pathogenesis of AAA is the angiotensin II (Ang II) infusion method delivered via osmotic mini-pump for 28 days. Here, we studied the site-specificity and onset of aortic rupture, characterized three-dimensional (3D) images and flow patterns in developing AAAs by ultrasound imaging, and examined macrophage infiltration in the Ang II model using 65 apolipoprotein E deficient mice. Aortic rupture occurred in 16 mice (25 %) and was nearly as prevalent at the aortic arch (44 %) as it was in the suprarenal region (56 %) and was most common within the first seven days after Ang II infusion (12 of 16; 75 %). Longitudinal ultrasound screening was found to correlate nicely with histological analysis and AAA volume renderings showed a significant relationship with AAA severity index. Aortic dissection preceded altered flow patterns and macrophage infiltration was a prominent characteristic of developing AAAs. Targeting the inflammatory component of AAA disease with novel therapeutics will hopefully lead to new strategies to attenuate aneurysm growth and aortic rupture.